Myocardial indium-111-antimyosin uptake in essential hypertension - Ünlü, M.; Temiz, N. H.; Hengel, A. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: Evaluation of myocardial uptake of 111In-anti-myosin antibodies in patients with essential hypertension for the verification of our hypothesis that it may increase in stage 1 in the left ventricle as a result of myocardial damage. Patients, methods: Twelve men (mean age: 59 ± 2.4 years) suffering from angina like symptoms and essential hypertension in clinical stage 1 according to the JNC-VI criteria were included into the study. These patients showed normal perfusion as revealed by thallium-201 myocardial study and coronary angiography. Left ventricular mass index was determined in echocardiography. Planar antimyosin images were obtained 48 h after the intravenous injection of the tracer. Heart to lung ratios were calculated as a parameter of myocardial tracer uptake using appropriate region of interests; values >1.52 were considered as abnormal. Results: We observed increased anti-myosin uptake (mean: 1.71 ± 0.12) consistent with myocardial damage in 11 of 12 patients. Nine of 12 patients had a left ventricular hypertrophy with left ventricular mass index values (mean: 131 g/m2 ± 9.48) above 115 g/m2. Heart to lung ratio was correlated significantly to left ventricular mass index (r = 0.902, p <0.001) and duration of hypertension (r = 0.948, p <0.001). Conclusion: Our results suggest that 111In-antimyosin imaging may indicate myocyte damage in early phases of hypertensive heart disease.
Keywords: Antimyosin; scintigraphy; hypertension; hypertrophy; echocardiography